Chitin-glucan complex – Based biopolymeric structures using biocompatible ionic liquids - Ferreira, Inês C. (2020)
This work explores the novelty of dissolving chitin-glucan complex (CGC), from two fungal strains, Komagataella pastoris (CGCP) and Aspergillus niger (CGCKZ) (KiOnutrime-CG™), using biocompatible ionic liquids (ILs). Three cholinium-based ILs were tested, choline acetate, choline propionate and choline hexanoate. Although all tested ILs resulted in the dissolution of the co-polymer at a concentration of 5 % (w/w), distinct polymeric structures, films or gels, were obtained from CGCP and CGCKZ, respectively. CGCP films were dense, flexible and elastic, with high swelling capacity (> 200 %). The IL anion alkyl chain length influenced the polymeric structures’ properties, namely, the CGCP films elongation at break and swelling degree. CGCKZ resulted in weak gels. For both polymeric structures, exposure to the ILs under the dissolution conditions caused significant changes in the co-polymers’ chemical structure, namely, reduction of their glucan moiety and reduction of the degree of acetylation, thus yielding chitosan-glucan complexes (ChGC) enriched in glucosamine (53.4 ± 0.3–60.8 ± 0.3 %)